THE ADAPTATION, VALIDITY TEST AND RELIABILTY CAREER MATURITY INVENTORY (CMI) ON JAKARTA HIGH SCHOOL STUDENT - Ni Made Taganing Kurniati; Dona Eka Putri; Wahyu Rahardjo; Hamdi Muluk; Tjut Rifameutia (Jurnal Psikologi, 2006)
The aim of this study is to adapt and measuring the validity and reliability of Career Maturity Inventory(CMI) created by John E. Crite. The goal of this research is a psychological inventory to measure thesenior high school students’ career maturity that already tested in Indonesian culture. The participantsof this research is 160 senior high school students in Jakarta with the sample comes from SMA KartiniJakarta and SMA 109 Jakarta. The research shows that only 30 items selected of attitude scale of CMIand 50 items selected of competency scale of CMI. The reliability for attitude scale of CMI is 0.708, andfor competency scale of CMI is 0.702. This results tell that CMI can be used as a tool in measuring thecareer maturity.Key words: career maturity, Career Maturity Inventory, career planning